Revenue Recognition Models Under International Financial Reporting Standard No. 15 And Polish National Accounting Standard No. 15 - Jaroslaw SZYSZKA (Communications of International Proceedings, 2024)
Despite the extraordinary relevance of revenues, their topic is too little addressed in the theoretical discussion of accounting. Now is a good time to revive the international discussion, since the first experience of applying IFRS No. 15 on revenue is already known. An additional motivation for the Author was the NAS on revenue published in his home country. The solutions contained therein are not the same as IFRS 15, which contributes to the discussion. In this article, the Author focused on the timing of revenue recognition - as this aspect was resolved differently in both standards. The article uses the method of source analysis, the method of historical analysis and the methods of deduction and induction. The author presented a historical outline of the approach to revenue in accounting, pointing out the dominant role of the balance sheet approach. He then presented the theories touching on the issue of when to recognize them, with particular emphasis on the contractual model (net position), which forms the basis of IFRS 15, and the risk-reward assumption model, which was adopted by the Polish NAS. The article concludes with a consideration of the implications of the two models adopted, which could be the beginning of further academic discussion.
Keywords: Revenue; accounting standards; moment of revenue recognition